Invisible man - Ellison, Ralph (Modern library of the world's best books., 1994)
After a brief prologue, the story begins with a terrifying experience from the hero's high-school days; it then moves quickly to the campus of a "Southern Negro college" and then to New York's Harlem, where most of the action takes place. The many people that the hero meets in the course of his wanderings are remarkably various, complex and significant. With them he becomes involved in an amazing series of adventures, in which he is sometimes befriended but more often deceived and betrayed - as much by himself and his own illusions as by the duplicity and the blindness of others. Invisible Man is not only a great triumph of storytelling and characterization; it is a profound and uncompromising interpretation of the anomalous position of Blacks in American society.